The Waal O-Antigen Lipopolysaccharide Ligase Has Features in Common with Metal Ion-Independent Inverting Glycosyltransferases - Perez-Donoso, J (2012)
WaaL is a membrane enzyme that catalyzes a key step in lipopolysaccharide (LPS) synthesis: the glycosidic bonding of a sugar at the proximal end of the undecaprenyl-diphosphate (Und-PP) O-antigen with a terminal sugar of the lipid A-core oligosaccharide (OS). Utilizing an in vitro assay, we demonstrate here that ligation with purified Escherichia coli WaaL occurs without adenosine-5?-triphosphate (ATP) and magnesium ions. Furthermore, E. coli and Pseudomonas aeruginosa WaaL proteins cannot catalyze ATP hydrolysis in vitro. We also show that a lysine substitution of the arginine (Arg)-215 residue renders an active protein, whereas WaaL mutants with alanine replacements in the periplasmic-exposed residues Arg-215, Arg-288 and histidine (His)-338 and also the membrane-embedded aspartic acid-389 are nonfunctional. An in silico approach, combining predicted topological information with the analysis of sequence conservation, confirms the importance of a positive charge at the small periplasmic loop of WaaL, since an Arg corresponding to Arg-215 was found at a similar position in all the WaaL homologs. Also, a universally conserved H[NSQ]X 9GXX[GTY] motif spanning the C-terminal end of the predicted large periplasmic loop and the membrane boundary of the transmembrane helix was identified. The His residue in this motif corresponds to His-338. A survey of LPS structures in which the linkage between O-antigen and lipid A-core OS was elucidated reveals that it is always in the ?-configuration, whereas the sugars bound to Und-PP are in the-configuration. Together, our biochemical and in silico data argue that WaaL proteins use a common reaction mechanism and share features of metal ion-independent inverting glycosyltransferases. © 2011 The Author.